Phylogenetic Characteristics of West Nile Virus Isolated From Culex modestus Mosquitoes in West Kazakhstan - Nurmakhanov, Talgat; Sansyzbaev, Yerlan; Atshabar, Boris; Berlin, Vladimir; Kobzhasarov, Damir; Yeskhojayev, Olzhas; Vilkova, Anna; Ayazbayev, Timur; Andryuchshenko, Alexey; Bidashko, Fyodor; Hay, John; Shvetsov, Alexandr (Frontiers in Public Health, 2021)
West Nile virus is widespread in southern Russia, where the fever appears annually. Since Western Kazakhstan borders on southern Russia, we examined mosquitoes in this region for the presence of West Nile virus. Virus was detected in a small proportion of Culex modestus mosquitoes (3/239 pools) and isolates are related to strains from Volgograd, Russia. A screen for West Nile virus IgG was conducted and 5% of the local human population tested positive.